A hybrid portrayal of visuospatial attention through eye tracking research and modular design / Shareefa Abdullah Ahmed Abdulmalek - Shareefa Abdullah , Ahmed Abdulmalek (2019)
In the art studio studies, a hybrid depiction of recognition phenomenology through art-science lab collaboration research has become a crucial issue in the course of producing hybrid artworks. Visuospatial attention in a choreographic dance video was selected as a case for depicting its form in this study. In the hybrid depiction, the challenging issue was how to visualise the indescribable features of invisible objects from its mental information through the pictorial source, transparency and experience domains. In order to address these problems, an approach Demonstrate, Resemble, and Synthesise DRS was proposed based on the combination between eye-tracking research, pattern modular design, and traditional art principles. This approach involved three stages of visualisation: gaze features demonstration stage, physical properties resemblance stage, and pictorial aspects synthesise stage were proposed in this study. The first stage was to demonstrate the gaze features of the specific case through fixation matrix feature output. It was implemented through an eye-tracking video-sections based experiment using the Tobii T60 eye tracker and StudioTM analysis software to collect and analyse the eye movements of ten international participants at the University of Malaya. Area of interest AOI statistics: AOI/gaze elicitation and AOI/pattern elicitation were used to identify the gaze qualities based on the fixation count and fixation length features. Results of this stage showed that the positive correlation and variety between features enable to use it as an information source for visualisation. The second stage was to resemble the physical properties using pattern modular design through additional table operation mod for visualising of the specific case. The properties width, height, color, pattern, frame, time, gist, space, and form were visualised. Outcomes showed that the patterns visualised have vertical geometrical forms. The final stage was to produce hybrid artworks through traditional art principles for the specific case. The balance and movement principles were selected and ten hybrid artworks were created in this research work. This thesis contributed to developing a novel proposed collaboration framework between experimental scientific approach as an information source, mathematical approach as a transparency and visual art as an experience for hybrid depiction.